Returns for entrepreneurs vs. employees: the effect of education and personal control on the relative performance of entrepreneurs vs. wage employees - C. Mirjam van Praag; Arjen van Witteloostuijn; Justin van der Sluis (Institute for the Study of Labor (IZA), 2009)
How valuable is education for entrepreneurs' performance as compared to employees'? What might explain any differences? And does education affect peoples' occupational choices accordingly? We answer these questions based on a large panel of US labor force participants. We show that education affects peoples' decisions to become an entrepreneur negatively. We show furthermore that entrepreneurs have higher returns to education than employees (in terms of the comparable performance measure 'income'). This is the case even when estimating individual fixed effects of the differential returns to education for spells in entrepreneurship versus wage employment, thereby accounting for selectivity into entrepreneurial positions based on fixed individual characteristics. We find these results irrespective of whether we control for general ability and/or whether we use instrumental variables to cope with the endogenous nature of education in income equations. Finally, we find (indirect) support for the argument that the higher returns to education for entrepreneurs is due to fewer (organizational) constraints faced by entrepreneurs when optimizing the profitable employment of their education. Entrepreneurs have more personal control over the profitable employment of their human capital than wage employees.
Keywords: J23; J24; J31; J44; M13; 330; Entrepreneurship; self-employment; returns to education; performance; personal control; locus of control; human capital; wages; incomes; Lohnniveau; Unternehmer; Selbstständige; Vergleich; Arbeitskräfte; Humankapital; Bildungsertrag; Berufswahl; USA